An Accurate, Affordable, and Precise Resazurin-Based Digital Imaging Colorimetric Assay for the Assessment of Fungicide Sensitivity Status of Fungal Populations - Silva, Tatiane Carla [UNESP]; Moreira, Silvino Intra [UNESP]; Assis, Fabio Gomes [UNESP]; Vicentini, Samara Nunes Campos [UNESP]; Silva, Abimael Gomes [UNESP]; Oliveira, Tamiris Yoshie Kitayama [UNESP]; Christiano, Félix Sebastião [UNESP]; Custódio, Adriano Augusto Paiva; Leite, Rui Pereira; Gasparoto, Maria Cândida Godoy [UNESP]; de Jesus, Waldir Cintra; Ceresini, Paulo Cezar [UNESP] (MDPI, 2023)
This study aimed at the development and validation of an accurate, more affordable, and precise digital imaging resazurin-based fungicide sensitivity colorimetric assay (COL-assay) for fungal plant pathogens from the genera Mycosphaerella and Pyricularia. This proposed digital imaging assay was based on colorimetric estimates of resazurin reduction, which was used as a metabolic indicator of fungal respiration activity on microplate cultures. As fungal model systems, we used the yellow and black Sigatoka pathogens [Mycosphaerella musicola (Mm) and M. fijiensis (Mf), respectively] and the wheat blast pathogen, Pyricularia oryzae Triticum lineage (PoTl), which were previously characterized for QoI, DMI, and SDHI fungicide sensitivity. We then compared the classical spectrophotometry detection assay (SPEC-assay) with the proposed COL-assay based on the analyses of digital images of the microplates’ cultures captured with mobile phone cameras on a handmade trans-illuminator built for poorly equipped labs. Qualitatively, in terms of accuracy, there was full correspondence between the SPEC-assay and the COL-assay according to the fungal EC50 or the relative growth classes on QoI, SDHI, and DMI fungicides for both Mycosphaerella and Pyricularia pathogens. We also observed a strong to very strong correlation coefficient between the COL-assay and the SPEC-assay fungicide sensitivity values for the QoI azoxystrobin, the SDHI fluxapyroxad, and the DMI tebuconazole. Our conclusion was that the COL-assay had a similar accuracy as the SPEC-assay (i.e., resulted in similar fungicide-sensitivity categories for both resistant or sensitive fungal isolates) and high precision. By openly sharing here the COL-assay’s full methodology, and the blueprints of the handmade trans-illuminator, we foresee its adoption by poorly equipped labs throughout the country as an affordable venue for monitoring the fungicide resistance status of populations of important fungal plant pathogens such as M. fijiensis, M. musicola, and P. oryzae Triticum and Oryza lineages.
Keywords: anti-microbial resistance phenotyping; DMI; fungal foliar pathogens; fungicide resistance; high-risk fungicides; limiting fungicide sprays; QoI; SDHI; smart anti-resistance strategies; surveillance-based spraying decision